Kesiapan Anggota KUD Dalam Menghadapi Replanting Kebun Kelapa Sawit Di Desa Kumain Kecamatan Tandun Kabupaten Rokan Hulu - Risman, Risman (Komunitas Manajemen Kompetitif, 2016)
Cooperative became the economic base of the people, for the cooperatives is the same interests and worked together. Cooperative oil palm plantations became very concerned at the time of replanting the gardens, the original members of the cooperative have a relatively large income, but the time period replanting becomes very difficult. The survey conducted to 30 farmer groups who joined the KUD in the village of Rokan Hulu Kumain explained that the factor of readiness of farmers, among others, the lack of readiness of the farmers themselves (4.503> 2.056 or 0.000 <0.05). Compared with KUD readiness factors and also other parties such as the foster father and banking. Keywords: Readiness Member, KUD